REPRESENTACIÓN DEL AUTISMO EN LAS SERIES DE NETFLIX. TRATAMIENTO DE LOS PERSONAJES. - TORRES BUENAIRE KEVIN ROLANDO (2024)
Currently, television series are seen on streaming platforms, with Max, Netflix and Disney + being the best known, but there is something that is not taken into account by consumers is the treatment of characters within the series, naturally it is a condition that is not taken with importance because characters with different illnesses, situations and conditions are usually represented in a way that is not so attached to reality. Since people who suffer from the aforementioned condition or illness and see that this situation is represented in a mocking or unserious tone depending on its degree of complexity, this project focuses on the treatment of autistic characters present in These series, five series are chosen which contain autistic people in their main or secondary cast to analyze them using an observation sheet to determine errors and look for adjustments without affecting the plot or essence of the series itself. Finally, a brief survey was carried out on a few communication students from the Technical University of Babahoyo to communicate the popular opinion about this issue.